Midwifery and Nursing Strategies to protect against COVID-19 During the Third Trimester of Pregnancy - Liu, Juan (Midwifery, 2021)
OBJECTIVE: The rapid pace of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic (COVID-19) presents significant challenges to midwives and nurses. This study aimed to explore midwifery and nursing interventions to limit the transmission of COVID-19 among women in their third trimester of pregnancy, to reduce the incidence of nosocomial infection and promote safety of care for women and their infants. METHOD: We completed a retrospective review of medical records from 35 women in their third trimester of pregnancy with SARS-CoV-2, admitted to one hospital in Wuhan, China in January and February 2020. We investigated the clinical characteristics of the COVID-19 infection in pregnancy, and the individualized midwifery and nursing care offered, including environmental protection, prevention of nosocomial infection, maternal observations, monitoring of signs and symptoms of COVID-19, and psychological care. RESULT: Thirty-one women had a caesarean section, and four had vaginal births. Retrospective analysis of midwifery and nursing strategies implemented to care for these women showed no maternal complications or nosocomial infections. CONCLUSIONS AND IMPLICATIONS FOR PRACTICE: The care strategies we implemented could prevent complications and nosocomial infection in the third trimester of pregnancy, thus ensuring the safety of women and their infants. Further research needs to determine treatment priorities for women infected with COVID-19 during pregnancy and the postnatal period.